The muvver tongue - MacNeil, Robert (Sydney, NSW. : BBC Education & Training, 1986)
Discusses the spread of the English language during the nineteeth century throughout the British Empire
Copy available in DVD format
Keywords: English language -- Commonwealth countries -- History; English language -- 19th century -- History